Treatment of Cholelithiasis with Choledocolytiasis through Videolaparoscopic Cholecystectomy (VLC) and Endoscopic Retrographic Charging (ERC) intraoperative in hospital in Alto Paranaíba – MG - Alcantara, Gabriel Maicow Silva (2021)
Introduction: Patients diagnosed with cholelithiasis, submitted to Laparoscopic Cholecystectomy, may present concomitant choledocholithiasis in an approximate proportion of 10 to 15% of the cases confirmed by the literature. However, there is still no consensus on the gold standard procedure for the management of cholelithiasis concomitant with choledocholithiasis. Associated with this, with the preference, both of patients and professionals, for minimally invasive and safer options for the treatment of cholelithiasis concomitant with choledocholithiasis, the ERCP associated with CVL is an option widely defended and accepted in several literature. Case Report: A. A. B., 35, sought hospital care with a typical picture of acute abdomen concomitant with jaundice. He performed abdominal ultrasound that diagnosed cholelithiasis and, subsequently, an MRI confirmed concomitant choledocholithiasis. Referred for surgery, he underwent a CPRE and CVL at one time. The patient was discharged the next day and recovered satisfactorily. Conclusion: With the complete success of the surgical procedure performed, it can be said that cholecystitis associated with choledocholithiasis, in fact, can be treated safely and effectively by means of a Retrograde Endoscopic Cholangiopancreatography concomitant with Laparoscopic Cholecystectomy in a single step.